Ethical, managerial and religious elements from the perspective of religious freedom (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2017)
The topic discussed here wants to highlight the elements of ethics and individual liberty through a theoretical and practical approach in order to create an argumentation that would motivate managerial involvement in terms of ethics and human rights. I have considered religious freedom could be considerate a very important step to financial success in a modern country. Romania must be considered the country of all Romanians no matter what religion they have. In this way Romanians must have the same rights in the society and economic life. Everyone should contribute to the well-being of the country.